Aktivisme Digital NCTzen dalam Kampanye Boikot Produk Pro-Israel (Studi Kasus pada Akun @nctzenhumanity) - Neng Desti Nur Laelasari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to determine the forms of interaction, participation, and motivation of Indonesian NCTzens in the boycott campaign of pro-Israel products through the @nctzenhumanity account on social media X. This study uses Henry Jenkins' theory of participatory culture and the concept of digital activism as the basis of analysis. The data for this study were obtained through semi-structured interviews with informants directly involved in the campaign, observations of campaign content, and digital documentation from the @nctzenhumanity account and related articles. Data validation techniques were carried out by triangulating sources to ensure the accuracy and consistency of the information obtained. The results showed that NCTzen interactions in the boycott campaign occurred through various activities, such as discussions, providing positive affirmations, and exchanging information that formed a virtual community. Their participation included digital actions such as retweets, raising hashtags, content creation, and sharing information that raised awareness about the boycott issue. In addition, real support was also given in the form of donations and boycotts of products originating from pro-Israel companies. Motivation for participation was driven by educational, moral, spiritual, emotional values, and fandom solidarity towards humanitarian issues. This campaign reflects the practice of participatory culture in fandom digital activism, where fandom transforms into an active social actor in the struggle for humanitarian issues through digital media.